APPLICATION OF TAGUCHI METHOD IN PRODUCTION OF SAMPLES PREDICTING PROPERTIES OF POLYMER COMPOSITES (Balkan Journal of Applied Mathematics and Informatics, 2018)
The purpose of the study is to access the applicability of Taguchi Method in predicting properties of polymer composites. The preparation of the composites was conducted by applying Taguchi L9 Method.  Voids are one of the most common defects in composite components and are known to degrade mechanical performance. As a result, void content measurement is often used both to assess the quality of a composite part and to determine its acceptability. For composites the calculate void in composite materials were determined in a lab according standard ASTM D 792, ASTM D 2734 and ASTM D 3171 with calculate experimental and theoretical density. From received results with minimal number of experiments and signal-to-noise ratios used as objective functions for optimization, data analysis and prediction of optimum results was shown that factor 1 has the biggest impact on the voids of manufacture samples.